Moderate cooling coprecipitation for extremely small iron oxide as a pH dependent T1-MRI contrast agent. Issue 9 (24th February 2020) - Chen, Bo; Guo, Zhanhang; Guo, Chunxian; Mao, Yu; Qin, Zhiguo; Ye, Dewen; Zang, Fengchao; Lou, Zhichao; Zhang, Zuoheng; Li, Mingyue; Liu, Yanlong; Ji, Min; et al.
Abstract : Moderate cooling coprecipitation for monodisperse extremely small iron oxide as a pH dependent T 1 -MRI contrast agent. Abstract : Iron based nanomedicine (IBNM) has been one powerful diagnostic tool as a magnetic resonance imaging (MRI) contrast agent (CA) in the clinic for years. Conventional IBNMs are generally employed as T 2 -MRI CAs, but most of them are constrained in clinical indication expansion by magnetic susceptibility artifacts. In comparison, extremely small iron oxide (ESIO) with a core size less than 5 nm has demonstrated the T 1 -MRI effect, which provides prospects for a Gd-based agent alternative. Nevertheless, currently developed ESIOs for T 1 -MRI CAs always require harsh conditions such as a high temperature and high boiling point reagent. Moreover, very few of the currently developed ESIOs meet the stringent pharmaceutical standard. Herein, on the basis of a crystal nuclear precipitation–dissolution equilibrium mechanism and outer/inner sphere T 1 -MRI theory, monodisperse ESIOs with an average size of 3.43 nm (polydispersity index of 0.104) are fabricated using a moderate cooling procedure with mild coprecipitation reaction conditions. The as-synthesized ESIOs display around 3-fold higher T 1 MRI signal intensity than that of commercial Ferumoxytol (FMT), comparable to that of Gd-based CAs in vitro . Additionally, the T 1 -MRI performance of the ESIOs is pH dependent and delivers bright signal augmentation. Eventually, the internalization into mesenchymal stem cells of the ESIO is realized in the absence of a transferring agent. Considering the identical structure and composition of the ESIOs as compared to that of FMT, they could meet the pharmaceutical criteria, thus providing great potential as T 1 -MRI Cas, for instance as stem cell tracers.